CRITICIZING THE BUGIS ISLAMIC SCRIPT, PAU-PAU RIKADONNA I DARAMATASIA FROM SIRIQ NA PESSÉ PERSPECTIVE - Bermawy Munthe; Mustari Mustari; Maharsi (IAIN Surakarta, 2021)
Pau-Pau Rikadonna I Daramatasia (PRID) is a very popular story and has an important position in the lives of Bugis people in South Sulawesi as well as in other region. In the script form, the story has three versions: Bone, Barru, and Pangkep. Not only being written in script form, the story is also staged in short films, picture stories, dances, and others. This article aims to understand the meaning for the Bugis' collective awareness of PRID stories. To reveal the meaning, Bone version of PRID will be used with considering the whole story. Bone's PRID is also unique because it has some additions of episodes at the beginning and at the end of the story that become the focus of this article analysis. In understanding the meaning contained in the PRID, Levi Strauss's theory of structuralism will be used by building binary opposition to the depth structure of the text. Based on the analysis conducted, the addition of episodes contained in the PRID version of Bone is closely related to the cultural value ofÂ siriq na pesseÂ (honor and solidarity) which is opposing sharia values. This can be interpreted as an effort by the Bugis to reconcile the two values so that PRID is well thanked and appreciated until now as can be seen in Youtube contents.